Citizens in policing: the lived reality of being a Police Support Volunteer - Millie, Andrew (Policing and society, 2019)
The focus of this article is the Police Support Volunteer (PSV), a brand of non-warranted and usually non-uniformed volunteer that was introduced in England and Wales from the 1990s onwards. The article draws on participatory action research with PSVs in Lancashire Constabulary. The background to greater use of volunteers within policing is discussed with particular reference to the political projects of austerity and responsibilisation - the later involving calls for citizens to take greater responsibility for their own safety and security. In these contexts, the article considers volunteers’ motivations, skills and deployment. The article focuses particularly on the lived reality of being a PSV, including the assumed role of PSVs within the wider police family. A subordinate relationship with other paid colleagues within the police family is challenged. The effective use of PSVs is discussed, including the introduction of police powers for volunteers with the 2017 Policing and Crime Act. Implications for our understanding of policing, and for the future of non-warranted volunteers, are discussed.